2015
DOI: 10.1177/0300060515587578
|View full text |Cite
|
Sign up to set email alerts
|

Health anxiety and depression in patients with fibromyalgia syndrome

Abstract: Objectives: To investigate health anxiety and depressive symptoms in patients with fibromyalgia syndrome (FMS). Methods: Patients with FMS and healthy control subjects were recruited. All participants completed the Health Anxiety Inventory Short Form (HAI-SF) and Beck Depression Inventory (BDI). Pain was assessed in patients with FMS using the Fibromyalgia Impact Questionnaire (FIQ) and Visual Analogue Scale (VAS). Results: This study involved 95 patients with FMS (15 male) and 95 healthy controls (17 male). M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
39
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 18 publications
6
39
1
2
Order By: Relevance
“…More specifically, the FMS group had significantly higher levels of depressiveness and anxiety (state and trait) than the healthy population [1,47]. As expected, the FMS patients also showed significantly higher scores of pain intensity.…”
Section: Discussionmentioning
confidence: 91%
“…More specifically, the FMS group had significantly higher levels of depressiveness and anxiety (state and trait) than the healthy population [1,47]. As expected, the FMS patients also showed significantly higher scores of pain intensity.…”
Section: Discussionmentioning
confidence: 91%
“…Indeed, a number of studies have shown a high prevalence of anxiety and depression in patients with fibromyalgia, in comparison with other chronic pain patients or healthy controls . Prevalence of emotional disorders is high, and depression has been reported in 20‐80% of cases whilst 13‐63.8% report anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings support prior research that have shown elevated rates of psychiatric disorders in people with MUS compared with those whose symptoms have a medical basis. Several studies, on patients with fibromyalgia, irritable bowel syndrome and unexplained chest pain have demonstrated increased rates of lifetime and current major depression as well as panic disorder . It has been shown that MUS patients with co‐morbid anxiety and depression have higher rates of dissatisfaction with treatment and are more likely to be perceived as difficult to treat by the physician .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies, on patients with fibromyalgia, irritable bowel syndrome and unexplained chest pain have demonstrated increased rates of lifetime and current major depression as well as panic disorder. [28][29][30] It has been shown that MUS patients with co-morbid anxiety and depression have higher rates of dissatisfaction with treatment and are more likely to be perceived as difficult to treat by the physician. 31,32 Interestingly, Walker and colleagues 33 showed that women who met criteria for both chronic pelvic pain and irritable bowel syndrome had higher rates of psychological distress than those with chronic pelvic pain alone.…”
Section: Discussionmentioning
confidence: 99%